Enhanced microwave-atom coupling via quadrupole transition-dressed Rydberg atoms - Du, Yijie; Cong, Nan; Liu, Yao; Lyu, Ziyao; He, Jun; Yang, Renfu (Frontiers in Physics, 2024)
The power broadening of a coupling laser can be converted into two-photon detuning by electromagnetically induced transparency (EIT), resulting in a residual Doppler effect. The residual Doppler effect in a ladder-type EIT in a room-temperature atom ensemble is further amplified through a wavelength mismatch effect between the probe and coupling laser beams, which reduces the atomic coupling of light or microwaves. We measured the Rydberg spectra of the electric dipole (E1) and electric quadrupole (E2) microwave transitions, demonstrating that the reduction in the Rydberg EIT signal can be recovered through far-off-resonance E2 microwave transition dressing and achieving an 8-dB enhancement in the Rydberg EIT signal. The frequency-dependent dressing of the E2 transition enables the shift of the dressed Rydberg states to be tuned, thereby providing a scalable approach to optimize the interaction between the Rydberg state and microwave field.broadening [10][11][12][13]. This residual Doppler effect is further amplified as the wave vector mismatch between the probe and the coupling laser, which reduces the atomic absorption [14][15][16].Recent studies on atomic clocks and interferometry have counteracted inhomogeneous broadening or shift using a magic or tune-out wavelength [17][18][19]. In these scenarios, multiple-field dressings allow the atomic degrees of freedom to be tuned and thereby improve coupling. More recent studies have used MW-dressed Rydberg atoms to tune atom-atom interactions [20][21][22]. These approaches have can also suppress spectral broadening or atomic decoherence [19,[23][24][25][26]; however, resonance transition dressings cause undesired Rydberg-state populations and introduce additional broadening. In contrast, far-off-resonance MW dressing offers an effective shift in the state but is less effective in modifying dressing polarization owing to its frequency insensitivity.In this study, an auxiliary field dressing for the electric quadrupole (E2) transition is used to counteract inhomogeneous spectral broadening. The reduction in atomic coupling of the optical and MW fields can be recovered by E2 transition dressing. The E2 transition modifies both the dressing shift and polarization. The dressing developed in this study provides a new method for recovering velocity-dependent residual Doppler effects in ladder-type EIT.